The management of mobile bearing dislocation in the Oxford lateral unicompartmental knee replacement. - Weston-Simons, J; Pandit, H; Gill, H; Jackson, W; Price, A; Dodd, C; Murray, D (2011)
This article describes a technique to manage dislocations of mobile bearing lateral unicompartmental knee replacements. When dislocations occur, the bearing usually subluxes medially over the medial wall of the tibial component into the intercondylar notch. By positioning small fragment screws with their heads above the vertical wall, thereby increasing the height of the wall, subsequent dislocations can be prevented. Seven cases treated in this manner are reported, of which one of the seven has redislocated. In the remaining six, their clinical outcomes are comparable to the outcomes of those without dislocations.